Hollow Biomass Adsorbent Derived from Platanus Officinalis Grafted with Polydopamine-Mediated Polyethyleneimine for the Removal of Eriochrome Black T from Water - Zefeng Jiang; Tongyang Song; Bowen Huang; Chengqiang Qi; Zifu Peng; Tong Wang; Yuliang Li; Linjing Ye (Molecules)
Platanus officinalis fibers (PFs) taking advantage of high-availability, eco-friendly and low-cost characteristics have attracted significant focus in the field of biomaterial application. Polyethyleneimine grafted with polydopamine on magnetic Platanus officinalis fibers (PEI-PDA@M-PFs) were prepared through a two-step process of mussel inspiration and the Michael addition reaction, which can work as an effective multifunctional biomass adsorbent for anionic dye with outstanding separation capacity and efficiency. The as-prepared PEI-PDA@M-PFs possess desirable hydrophilicity, magnetism and positive charge, along with abundant amino functional groups on the surface, facilitating efficient adsorption and the removal of Eriochrome Black T (EBT) dyes from water. In addition to the formation mechanism, the adsorption properties, including adsorption isotherms, kinetics, and the reusability of the absorbent, were studied intensively. The as-prepared PEI-PDA@M-PFs achieved a theoretical maximum adsorption capacity of 166.11 mg/g under optimal conditions (pH 7.0), with 10 mg of the adsorbent introduced into the EBT solution. The pseudo-second-order kinetic and Langmuir models were well matched with experimental data. Moreover, thermodynamic data ΔH > 0 revealed homogeneous chemical adsorption with a heat-absorption reaction. The adsorbent remained at high stability and recyclability even after five cycles of EBT adsorption processes. These above findings provide new insights into the adsorption processes and the development of biologic material for sustainable applications.